Molecular cytogenetic characterisation of a small ring X chromosome in a Turner patient and in a male patient with congenital abnormalities: role of X inactivation. Issue 2 (February 1995) - Callen, D F; Eyre, H J; Dolman, G; Garry-Battersby, M B; McCreanor, J R; Valeba, A; McGill, J J
Abstract : The association of small accessory marker chromosomes in man with specific abnormalities has been difficult to define owing to variations in the chromosome origin and the size of the markers. In a patient with typical Turner phenotype and a 45, X/46, X, + mar karyotype the marker was shown to be a small portion of the long arm of the X chromosome which included the centromere and XIST, a candidate gene for the X inactivation centre. Therefore the lack of any additional abnormalities was attributed to inactivation of the portion of the X chromosome in the marker. In a patient with a 47, XY, + mar karyotype the mar was a small ring X chromosome which did not contain the XIST gene. For both markers the short arm breakpoints were localised between UBE1 and DXS423E. The congenital abnormalities of the male patient were attributed to the lack of X inactivation of the small ring and therefore disomic expression of normal genes possessed by the marker.